Questioning the therapeutic value of corticosteroid bursal injection after ultrasound-guided irrigation and lavage for the treatment of shoulder calcific tendinosis - Malahias, Michael-Alexander (J Orthop, 2019)
OBJECTIVES: The therapeutic value of corticosteroid bursal injection after ultrasound-guided irrigation and lavage for the treatment of shoulder calcific tendinosis has not been established yet in the long term. METHODS: 41 patients suffering from chronic symptomatic rotator cuff calcific tendinopathy were recruited for this study. Group A (20 patients) received a double needle ultrasound-guided irrigation and lavage of the calcification with xylocaine injection, while group B (21 patients) underwent a double needle ultrasound-guided irrigation and lavage of the calcification with a xylocaine and betamethazone bursal injection. RESULTS: After twelve months, we documented full –or almost full- decline (VAS: 0–20/100) of the symptoms in 70% of the group A patients and in 61.9% of the group B patients. There was no statistical difference (chi square, p < 0.05) in group success ratio. We also did not find any statistical difference as for the mean Q-DASH difference between the two groups (t-test). CONCLUSIONS: It was proven that the additional use of corticosteroid bursal injection did not provide with any additional short- to mid-term therapeutic benefit those patients with shoulder calcific tendinopathy who were treated with ultrasound-guided aspiration.